The fall [compact disc, unabridged] : a novel - Lescroart, John T. (Brilliance Audio, 2015)
Late one night, a teenage African American foster child named Tanya Morgan plummets to her death from the overpass above San Francisco's Stockton tunnel. But did she fall...or was she pushed? Rushing to produce a convictable suspect in the glare of the media spotlight, homicide inspectors focus their attention on a naive young man named Greg Treadway.